Promotion effect of the blend containing 2'-FL, OPN and DHA on oligodendrocyte progenitor cells myelination in vitro - Xie, Qinggang; Zhang, Youbo; Zhang, Jinlan; Cui, Dongying; Zhou, Qile; Guo, Mingruo (Frontiers in Nutrition, 2022)
During early neurodevelopment of infant, myelination plays an essential role in brain connectivity and emergence of behavioral and cognitive function. Early life nutrition is an important factor to shape myelination and consequently cognitive appearance. To analyze the effects of additive nutrients, including 2'-fucosyllactose (2'-FL), osteopontin (OPN), docosahexaenoic acid (DHA), on neurocognitive function and brain structure, the current study evaluated the effects of different composition of breast milk nutrients on oligodendrocyte progenitor cells (OPCs) myelination with a neural primary cell model in vitro. The study showed that the three nutrients promoted the proliferation, maturation and differentiation of OPCs into mature oligodendrocytes (OLs) in each phage of the cell growth, and the effect of the nutrients blend is obviously stronger than that of the nutrient treatment alone, showing a synergistic effect in promotion of OPCs. The results of this experiment clarified the effects of 2′-FL OPN and DHA to promote myelination development of neural cells, and laid an experimental basis for further optimization of infant formula.